2021
DOI: 10.1155/2021/8883933
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Emergency Department Wait Times Information: A Patient-Centered Needs Assessment

Abstract: Introduction. Many Emergency Departments (ED) publish wait times; however, the patient perspective in what information is requested and the quantity of information to post is limited. Methods. We conducted a mixed-methods study at a tertiary care academic center. First, we conducted focus groups of 7 patients. We then generated themes following content analysis to create a patient survey. We administered in-person surveys to patients in ED waiting rooms at sites randomized for survey administration. We used pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There is literature present on the correlations between longer wait times and lower perceived care quality in both the outpatient clinical setting and the emergency department [10]. Given this information, as well as the patient preference for knowing emergency department waiting times, the implications of this study may be useful in guiding consumer decision making [8]. Given that academic hospitals have displayed statistically greater wait times before admission as well as time till sent home, patients may choose to factor this into decision making prior to going into a hospital.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is literature present on the correlations between longer wait times and lower perceived care quality in both the outpatient clinical setting and the emergency department [10]. Given this information, as well as the patient preference for knowing emergency department waiting times, the implications of this study may be useful in guiding consumer decision making [8]. Given that academic hospitals have displayed statistically greater wait times before admission as well as time till sent home, patients may choose to factor this into decision making prior to going into a hospital.…”
Section: Discussionmentioning
confidence: 94%
“…A 2021 publication by Calder-Sprackman et al suggested that patients like being able to know emergency department wait times prior to going to the hospital. In fact, patients felt greater quality care when they knew the waiting time [8]. Hospitals have taken note of the importance of wait times and are taking steps to reduce waiting times.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing a team approach to improve communication (e.g., attending physician asking resident to update family regarding lab results while reviewing another patient with a different trainee), we may be able to meet family needs better, without losing time efficiencies. Other communication avenues that spare time-loss could include innovative digital adaptations that allow families to see wait times or access their own lab results [29]. These findings underscore the importance of caregiver involvement in their child's care and adequate communication by ED staff as critical driving factors in improving emotional and communication needs and satisfaction with care for caregivers in the ED.…”
Section: Plos Onementioning
confidence: 88%
“…70 Relatedly, patients perceive displaying wait times as positive and needed. 71 Triage of frequent attenders has also been noted as important. Roughly one in five of all ED visits are from frequent attenders, 72 and this patient group often feels that healthcare professionals lack empathy and downplay their needs.…”
Section: Discussionmentioning
confidence: 99%